Fuel Net: Artificial Intelligence Tool for Fuel Consumption Prediction in Heavy Vehicles (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This project aims to develop one such solution by utilizing the FuelNet model, which focuses on predicting and enhancing fuel efficiency in heavy vehicles. By analyzing real-time data and historical patterns, FuelNet can accurately predict fuel consumption, empowering fleet operators and logistics companies to optimize their operations and reduce operating costs. Compared to traditional manual methods, this AI-powered tool represents a significant improvement, offering adaptability, precision, and a commitment to environmental sustainability in heavy vehicle operations. As the world increasingly emphasizes eco-friendly and cost-effective transportation solutions, FuelNet emerges as a key technology driving the transport industry towards a greener and more efficient future. By leveraging the power of AI, we can make substantial strides in improving fuel efficiency, reducing emissions, and promoting a more sustainable transportation system.